Biomass production of Azolla microphylla as biofilter in a recirculating aquaculture system - SUMOHARJO, SUMOHARJO; MA’RUF, MOHAMMAD; BUDIARTO, IRWAN (Society for Indonesian Biodiversity & Universitas Mulawarman, Samarinda, Indonesia, 2018)
Sumoharjo, Ma’ruf M, Budiarto I. 2018.Biomass production of Azolla microphylla as biofilter in a recirculating aquaculture system. Asian J Agric 2: 14-19. This study utilized macrophyte (Azolla microphylla Kaulf.) as biofilter and perhaps that biomass produced in aquaculture system can be potential for alternative feed. This experiment such a first step of that vision and was aimed to determine the Azolla microphylla growth rate and its efficiency in removing ammonia from a simple recirculating aquaculture system. The experimental units were set up in three different water flow, i.e. 3 lpm, 5 lpm, and 7 lpm onto the three different geometrically baseboard of Tilapia (Oreochromis niloticus) growing tanks (prism, rectangular and limas).The result showed that water flow did not give significant effect(P < 0.10) on the growth rate of Azolla.The lower water flow (3 lpm) resulted in the highest amonia biofiltration efficiency which can remove ammonia up to 32.2±3.0% of the total NH3-N and NH4+-N (TAN).